2009
DOI: 10.1103/physrevd.80.014504
|View full text |Cite
|
Sign up to set email alerts
|

Equation of state and QCD transition at finite temperature

Abstract: We calculate the equation of state in 2+1 flavor QCD at finite temperature with physical strange quark mass and almost physical light quark masses using lattices with temporal extent Nτ = 8. Calculations have been performed with two different improved staggered fermion actions, the asqtad and p4 actions. Overall, we find good agreement between results obtained with these two O(a 2 ) improved staggered fermion discretization schemes. A comparison with earlier calculations on coarser lattices is performed to qua… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

55
665
9
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 526 publications
(731 citation statements)
references
References 42 publications
55
665
9
2
Order By: Relevance
“…It is tempting to attribute these two phenomena to a single underlying mechanism, an idea supported by finite-temperature studies where the deconfinement and chiral restoration transitions are observed to occur at similar temperatures [1][2][3]. Lowlying modes of the quark operator, known to dominate D SB, are also correlated with the finite-temperature transition of the Polyakov loop, and hence confinement [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…It is tempting to attribute these two phenomena to a single underlying mechanism, an idea supported by finite-temperature studies where the deconfinement and chiral restoration transitions are observed to occur at similar temperatures [1][2][3]. Lowlying modes of the quark operator, known to dominate D SB, are also correlated with the finite-temperature transition of the Polyakov loop, and hence confinement [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, we list review articles and textbooks which cover applications of AdS/CFT [18,19,20,21,22,23,24,25,26]. These cover the materials which are not covered in this book and are useful complements.…”
Section: Some Useful Textbooks and Prerequisitesmentioning
confidence: 99%
“…So far we have not specified the form of the metric, but the metric is determined by the Einstein equation 3 : 26) where G is the Newton's constant, and T µν is the energy-momentum tensor of matter fields. The Einstein equation claims that the spacetime curvature is determined by the energy-momentum tensor of matter fields.…”
Section: Einstein Equation and Schwarzschild Metricmentioning
confidence: 99%
See 2 more Smart Citations